ChemInform Abstract: A Highly Regio‐ and Stereoselective Selenoxide Elimination of 1, 2‐Bis[4‐(trimethylsilyl)phenylseleno]alkanes to Give (E)‐Alkenyl Selenoxides and Its Mechanistic Study. Issue 26 (June 2016) - Tarao, Asami; Niki, Aya; Komagawa, Shinsuke; Arimitsu, Kenji; Uchimoto, Hitomi; Kawasaki, Ikuo; Yamaguchi, Kentaro; Nishide, Kiyoharu
Abstract: Oxidation of organo‐selenium compounds (I) with MCPBA generates bisselenoxide intermediates which undergo elimination to give products (II) with high regio‐ and E/Z‐selectivity.